Pengaruh Pengungkapan ESG dan Manajemen Laba terhadap Biaya Modal Ekuitas pada Sektor Perbankan - Tiwi Riyanti; Muhammad Fahmi; Ayu Umyana (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) and earnings management on the cost of equity capital in banking companies listed on the Indonesia Stock Exchange for the 2022–2024 period. The study uses a causal associative quantitative method with secondary data obtained from annual reports and sustainability reports. The research sample was determined using purposive sampling and resulted in 38 banking companies with a total of 114 observations. The data analysis technique was carried out using panel regression using EViews 12 with a Random Effects Model selected based on the Chow Test, Hausman Test, and Lagrange Multiplier Test. The research findings indicate that ESG has a negative and significant impact on the cost of equity capital, while earnings management has a positive and significant impact on the cost of equity capital. The control variables of company size and Capital Adequacy Ratio (CAR) have a negative and significant impact on the cost of equity capital. Simultaneously, all research variables have a significant impact on the cost of equity capital in banking companies. This study makes an empirical contribution by expanding the evidence regarding the impact of ESG disclosure and earnings management on the cost of equity capital in the Indonesian banking sector during the post-COVID-19 pandemic period. The findings are expected to serve as a reference for investors, corporate management, and regulators in enhancing transparency, reporting quality, and investment decision-making.